The TKFC Ala185Thr variant, reported as 'null' for fructose metabolism, is fully active as triokinase. Issue 11 (10th February 2022) - Ribeiro, João M.; Costas, María Jesús; Cabezas, Alicia; Meunier, Brigitte; Onoufriadis, Alexandros; Cameselle, José Carlos
Abstract : TKFC ‐encoded triokinase catalyses glyceraldehyde phosphorylation in fructose metabolism and favours lipogenesis in mice. In Tkfc knockouts or knockdowns, fructose oxidation predominates over lipogenesis. The highly prevalent human variant Ala185Thr‐Triokinase/FMN cyclase (TKFC) has been reported to be 'null' for fructose metabolism, since Ala185‐TKFC rescues the mouse TKFC‐deficient phenotype, whereas Ala185Thr‐TKFC does not. Such report implies that most humans would display a noncanonical fructose metabolism, but it ignores the well‐characterized triokinase activity of Ala185Thr‐TKFC. Here, earlier evidence is summarized, along with new evidence that both human variants are equally active in yeast. Therefore, future research on triokinase in the context of human fructose metabolism should consider that Ala185Thr‐TKFC is not biochemically 'null'. Abstract : The triokinase TKFC catalyses the final step in fructose metabolism by phosphorylating d ‐glyceraldehyde (triokinase activity). Two human variants differing in amino acid 185 are known: Ala185‐TKFC and Thr185‐TKFC. The latter, reported as 'null' for fructose metabolism, has a frequency of 0.92, suggesting altered metabolism in most individuals. However, here, we summarize earlier and new evidence against Thr185‐TKFC being biochemically 'null', as it displays full triokinase activity.